German Rabbis in British Exile : From ‘Heimat’ into the Unknown - Zajdband, Astrid (De Gruyter eBook-Paket Geschichte, 2016)
The rich history of the German rabbinate came to an abrupt halt with the November Pogrom of 1938. Many rabbis obtained visas and came to Britain and participated in the re-shaping of the Anglo-Jewish landscape. They supported their fellow refugees with spiritual and pastoral care and founded institutions and organizations, such as the Leo Baeck College in London. This created new impetus for Anglo-Jewry, an influence that can still be felt today.